The Influence of Human Resource Development and Leadership on Employee Performance with Work Commitment as a Mediation (International Journal of Economics and Management Research, 2026)
Frentho Valentino Efrath Reinati (Master of Management, Universitas Widya Gama Malang, 2025) entitled "The Effect of Human Resource Development and Transformational Leadership on Employee Performance with Work Commitment as a Mediator (Study at the Kupang City Civil Registration Office)", aims to analyze the direct and indirect effects between human resource development (HRD), transformational leadership, work commitment, and employee performance. This study uses an explanatory approach with a survey method on all employees of the Kupang City Civil Registration Office, totaling 77 respondents (saturated sample). Data analysis was carried out using Partial Least Square (PLS). The results of the study indicate that human resource development significantly influences employee performance and work commitment, while work commitment does not significantly influence employee performance. Furthermore, transformational leadership significantly influences work commitment, but does not directly influence performance. As a mediator, human resource development through work commitment does not significantly influence performance, while transformational leadership through work commitment significantly influences employee performance. These findings underscore the importance of human resource development and transformational leadership styles in improving public apparatus performance.